783Lifetime alcohol intake and stomach cancer risk: a pooled analysis of two prospective cohort studies. (2nd September 2021) - Jayasekara, Harindra; MacInnis, Robert; Yang, Yi; Hodge, Allison; Mitchell, Hazel; Haydon, Andrew; Room, Robin; Hopper, John; Gunter, Marc; Riboli, Elio; Giles, Graham; Milne, Roger; et al.
Abstract: Background: Alcohol consumption is causally linked to several cancer sites but the evidence for stomach cancer is still inconclusive. We aimed to quantify the association between alcohol intake and risk of stomach cancer, including subtypes. Methods: We pooled data from two cohort studies including 452, 958 individuals enrolled in the European Prospective Investigation into Cancer in 1992-98 and 38, 756 Australians enrolled in the Melbourne Collaborative Cohort Study in 1990-94. Adjusted hazard ratios (HR) and 95% confidence intervals (CI) for incident stomach cancer were estimated using Cox regression. Results: 1, 225 incident stomach cancers were diagnosed over 7, 094, 637 person-years. Alcohol intake was not associated with overall stomach cancer risk. We observed a weak positive dose-response association for lifetime intake with non-cardia stomach cancer (HR = 1.03, 95% CI: 1.00-1.06/per 10 g/day increment), which is the more common type (77.6% of cases), and a weak inverse association with cardia cancer (HR = 0.93, 95% CI: 0.87-1.00) ( p homogeneity =0.006). These associations did not differ appreciably by smoking or Helicobacter pylori infection status. Differences in HRs between diffuse-type and intestinal-type cancer were minimal ( p homogeneity =0.97). HRs of 1.50 (95% CI: 1.12-2.01) for non-cardia and 0.53 (95% CI: 0.27-1.02) for cardia cancer were observed for a life course trajectory characterised by sustained heavy drinking compared with light drinking ( p homogeneity =0.01). Conclusions: Lifetime alcohol intake was associated with increased risk of non-cardia stomach cancer. The inverse association for cardia cancer indicates aetiologic differences between subsites. Key messages: Limiting long-term alcohol consumption, and avoiding heavy use in particular, might be beneficial in preventing non-cardia stomach cancer.